Cell-penetrating self-nanoemulsifying drug delivery systems (SNEDDS) for oral gene delivery. (1st November 2016) - Mahmood, Arshad; Prüfert, Felix; Efiana, Nuri Ari; Ashraf, Muhammad Imtiaz; Hermann, Martin; Hussain, Shah; Bernkop-Schnürch, Andreas
ABSTRACT: Objective : The aim of study was to investigate whether cell-penetrating peptides could amplify cellular uptake of plasmid DNA (pDNA) loaded self-nanoemulsifying drug delivery systems (SNEDDS) by mucosal epithelial cells, thereby enhancing transfection efficiency. Methods : HIV-1 Tat peptide-oleoyl conjugate (TAT-OL) was synthesized through amide bond formation between HIV-1 Tat-protein 49–57 (TAT) and oleoyl-chloride (OL). SNEDDS formulation contained 29.7% each of Cremophor EL, Capmul MCM and Crodamol, 9.9% propylene glycol and 1% TAT-OL. SNEDDS with OL instead of TAT-OL served as control. Results : Fluorescent-microscopy demonstrated 0.5% (m/v) nanoemulsions were suitable for subsequent studies. Mucus diffusion of nanoemulsion loaded with fluorescein diacetate (FDA) was 1.5-fold increased by incorporation of TAT-OL. Confocal microscopy confirmed that droplets of nanoemulsions were successfully internalized. Furthermore, quantitative analysis showed that addition of TAT-OL increases uptake of nanoemulsions by 2.3- and 2.6-folds after 2 and 4 hours of incubation, respectively. Cellular internalization pathways were found with substantial decrease in uptake in presence of indomethacin and chlorpromazine. Transfection efficiency investigated on HEK-293-cells was found to be 1.7- and 1.8-fold higher for SNEDDS loaded with TAT-OL compared to Lipofectin and control, respectively. Conclusion : In comparison to prevailing lipid and polymer-based delivery systems, these novel cell-penetrating SNEDDS likely represent most effective, simplistic and expedite dosage form for mucosal gene delivery.